Paideia Mitopoética: a educação em Tolkien - Klautau, Diego Genu (2012)
This thesis is a systematic exposition of the theory of the education existent in the production of J.R.R Tolkien, that we call of Mythopoetic Paideia. From a phenomenological hermeneutics of its works of philological medieval poem analysis, of its theoretical assay on literature, its mythopoetics novels and its personal letters, we systemize a theory of the composed education of clear concepts of subject, object and method. In this theory, there is an anthropology that dialogues with the philosophical tradition Greek, the patristic and the scholastic, and that it is harmonic with the phenomenology of century XX; in the same way, the basic object is the sacred, understood as category of sciences of the religion, in historical and noetic key, that if express through the sacred narratives, either in the forms of the alive myth, either in the forms of the mythical reminiscences of the epic poetry or the modern romances of fancy. The method is the myth manufacture as form of meditation of the reading of texts of religious traditions, as well as the dialogic sharing with a group, that culminates in the publication of the manufactured workmanship. Thus, the subject that is open to the experience of the totality of the Being through the hierofania through poetical or literary narrative, through a method that integrates tradition, communion, creativity and work, makes acquaintance with the founding object of the conscience and the culture: the sacred